1992
DOI: 10.1017/s0022029900027187
|View full text |Cite
|
Sign up to set email alerts
|

Low-field nuclear magnetic resonance relaxation study of thermal effects on milk proteins

Abstract: SUMMARY. A recently described nuclear magnetic resonance (NMR) method was evaluated for its usefulness in studying thermal effects on milk proteins. The increase in water proton T 2 relaxation rate observed during thermal treatment of aqueous whey protein solutions above the denaturing onset temperature paralleled results obtained with the standard Rowland (1938) method. The influence of milk constituents on NMR characteristics was analysed. The NMR response increased with the ionic strength and the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Although several investigators23–25, 37 have suggested that low‐field NMR can be used to study protein denaturation, the results of this study indicate that it cannot be used to study the denaturation of β‐LG. Instead it can be used to study its aggregation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although several investigators23–25, 37 have suggested that low‐field NMR can be used to study protein denaturation, the results of this study indicate that it cannot be used to study the denaturation of β‐LG. Instead it can be used to study its aggregation.…”
Section: Discussionmentioning
confidence: 69%
“…Thermal denaturation led to aggregation and integration of water into the protein structure, and also affected the two time constants. Lambelet et al 24,25 observed a significant change in T 2 of globular whey proteins at about 70 • C, which is close to their denaturation temperature. They observed the change even at low protein concentrations where gelation is unlikely to occur and concluded that the change in T 2 was due to protein unfolding.…”
Section: Introductionmentioning
confidence: 78%
“…The application of LR NMR to study whey proteins and the influence of processing on structure-formation is not often found in literature. The denaturation of whey protein in combination with casein (Lambelet, Berrocal, & Renevey, 1992), the rehydration of milk powders (Davenel, Schuck, & Marchal, 1997;Davenel, Schuck, Mariette, & Brul! e, 2002) and the influence of different milk components, including whey protein, on water (Le Dean, Mariette, Lucas, & Marin, 2001) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The denaturation of whey proteins is more pronounced at low pH. Changes in the transverse relaxation rates due to whey protein denaturation have been reported (Lambelet, Berrocal, & Renevey, 1992). The significant reduced relaxation times in the sample with low pH, without added NaCl and with UHPH treatment must in some way be related to the higher viscosity of the sample, but the comparable sample with high mineral content also showed high viscosity but relaxation times in line with the rest of the experimental design.…”
Section: Low Field Nuclear Magnetic Resonancementioning
confidence: 76%